Ligamentäre Verletzungen und Bandinstabilitäten der Fingergelenke = Ligamentous lesions and instability of the finger joints - Spies, Christian; Langer, Martin Franz; Müller, Lars Peter; Oppermann, J.; Löw, Steffen; Unglaub, Frank (Der Orthopäde, 2018)
Joint capsule and ligamentous lesions are common injuries of the upper extremities. Athletes are particularly inclined to suffer from these injuries. Clinical and radiological examinations are the cornerstone of an adequate treatment. Ultrasound-based diagnostics as a non-invasive and dynamic investigation method are gaining increasing relevance based on the development of high resolution probes. A correct interpretation of the findings is only feasible with a comprehensive knowledge of the anatomy. The most important goal is stability as a prerequisite for early active and passive motion with unrestricted range of motion.
Published online: 20 December 2017
Gesehen am 02.04.2020